Assessing Ecological Recovery of Reclaimed Well Sites: A Case Study From Alberta, Canada - Baah-Acheamfour, Mark; Dewey, Mark; Fraser, Erin C.; Schreiber, Stefan G.; Schoonmaker, Amanda (Frontiers in Forests and Global Change, 2022)
Empirical evaluations of reclamation success are critical for understanding the speed of ecosystem recovery and improving best practices. In this study, we provide a quantitative evaluation of the effectiveness of past (pre-1995) and current (2010) reclamation criteria in creating functioning forest ecosystems on former industrial sites in boreal Alberta, Canada. We compared ecological indicators of ecosystem recovery (vegetation structure and soil properties) on mineral surface leases (MSLs) certified to the pre-1995 or 2010 reclamation criteria with nearby reference areas recovering from harvest (CUT) or fire (FIRE) disturbances. Six CUT and FIRE sites were chosen to compare to six 1995MSLs and five 2010MSLs. Averaging 8 years since reclamation, most of the 2010MSLs were characterized by many of the same vegetation structure and soil properties as the FIRE and CUT sites. The 1995MSLs tended to support more agronomic species, notably grasses and non-native forbs, and fewer shrubs, trees, and native forbs than CUT or FIRE sites. Sites with the greatest coverage of herbaceous species (native and non-native grasses as well as non-native forbs) were the most ecologically impaired sites, based on the extreme deviation from reference site conditions. Based on these results, the 2010 reclamation criteria appear to be more effectively promoting ecosystem recovery on reclaimed industrial sites than the pre-1995 criteria. While this case study illustrated the potential benefits of straightforward changes to reclamation criteria in terms of including metrics around soil quality and conservation, woody stem requirements and native plant coverage, there is ultimately always room for improvement. For jurisdictions where the objective of the criteria is to restore a forest ecosystem, including criteria geared towards tree establishment would likely be of value in ensuring the speedy return to a forest canopy state. Adding criteria with measures of native plant species diversity may also be of utility as it is well understood that having plant diversity is also a beneficial metric in creating a more resilient vegetation community.